2014
DOI: 10.1038/srep04780
|View full text |Cite
|
Sign up to set email alerts
|

Single cell genome analysis of an uncultured heterotrophic stramenopile

Abstract: A broad swath of eukaryotic microbial biodiversity cannot be cultivated in the lab and is therefore inaccessible to conventional genome-wide comparative methods. One promising approach to study these lineages is single cell genomics (SCG), whereby an individual cell is captured from nature and genome data are produced from the amplified total DNA. Here we tested the efficacy of SCG to generate a draft genome assembly from a single sample, in this case a cell belonging to the broadly distributed MAST-4 uncultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 53 publications
4
47
0
Order By: Relevance
“…To overcome this limitation, Single Cells Genomics is a very promising approach2829. However, this approach has been largely used for bacteria30 and numerous technical challenges have limited the recovery of eukaryotic genomes with this approach28313233. The most complete assembly obtained so far is for an uncultured stramenopile belonging to the MAST-4 clade and contains about one third of the core eukaryotic gene set33.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this limitation, Single Cells Genomics is a very promising approach2829. However, this approach has been largely used for bacteria30 and numerous technical challenges have limited the recovery of eukaryotic genomes with this approach28313233. The most complete assembly obtained so far is for an uncultured stramenopile belonging to the MAST-4 clade and contains about one third of the core eukaryotic gene set33.…”
mentioning
confidence: 99%
“…However, this approach has been largely used for bacteria30 and numerous technical challenges have limited the recovery of eukaryotic genomes with this approach28313233. The most complete assembly obtained so far is for an uncultured stramenopile belonging to the MAST-4 clade and contains about one third of the core eukaryotic gene set33. Recently, the Tara Oceans expedition collected water samples from the photic zone of hundreds of marine sites from all oceans and obtained physicochemical parameters, such as silicate, nitrate, phosphate, temperature and chlorophyll343536.…”
mentioning
confidence: 99%
“…SNVs in kidney tumor MDA Xu et al, 2012 Tumor evolution in breast cancer DOP-PCR Navin et al, 2011 Tumor evolution in breast cancer MDA Wang et al, 2014b Tumor evolution in myeloproliferative neoplasm MDA Hou et al, 2012 CTCs in lung cancer MALBAC Ni et al, 2013 Recombination and aneuploidy in human sperm MALBAC Lu et al, 2012 Recombination and mutation in human sperm MDA Wang et al, 2012 The triads of the first and second polar bodies and oocyte pronuclei MALBAC Hou et al, 2013 Mosaic CNVs in human neurons MDA McConnell et al, 2013 Uncultivable microbes MDA Marcy et al, 2007b;Marshall et al, 2012 Uncultivable protists MDA Yoon et al, 2011;Roy et al, 2014 Single-cell transcriptomic sequencing…”
Section: Single-cell Genomic Sequencingmentioning
confidence: 98%
“…This is especially challenging when dealing with eukaryotic organisms because their genomes are larger than bacterial genomes and can have long repetitive stretches. Recent studies have found that genome recovery per SAG for MAST-4 flagellate cells ranged between 20 and 40% (Roy et al 2014, Mangot et al 2017. This means that during traditional MDA-based SAG sequencing, not only is a fraction of the host genome missed, but also the genomes of its symbionts can be underrepresented or totally missed.…”
Section: Single-cell Genomicsmentioning
confidence: 99%